2020
DOI: 10.12688/f1000research.23635.1
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific mitochondrial gene variation can be as low as that of nuclear rRNA

Abstract: Background: Mitochondrial DNA (mtDNA) has long been used to date historical demographic events. The idea that it is useful for molecular dating rests on the premise that its evolution is neutral. Even though this idea has long been challenged, the evidence against clock-like evolution of mtDNA is often ignored. Here, we present a particularly clear and simple example to illustrate the implications of violations of the assumption of selective neutrality. Methods: DNA sequences were generated for the mtDNA COI g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…While single‐locus data has its limitations in making inferences about historical demography (Matumba et al, 2020), DNA barcoding, or the use of other single‐locus DNA markers, has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Bousjein et al, 2021; León‐Tapia, 2021; Nneji et al, 2020; Sholihah et al, 2020; Wang et al, 2020). These data are particularly helpful when aiming to explore broad‐scale patterns such as those on a continental scale (Dincă et al, 2021) or across species (Doorenweerd et al, 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…While single‐locus data has its limitations in making inferences about historical demography (Matumba et al, 2020), DNA barcoding, or the use of other single‐locus DNA markers, has provided tremendous insight into identifying evolutionary significant units and providing information on species in further need of exploration (Bousjein et al, 2021; León‐Tapia, 2021; Nneji et al, 2020; Sholihah et al, 2020; Wang et al, 2020). These data are particularly helpful when aiming to explore broad‐scale patterns such as those on a continental scale (Dincă et al, 2021) or across species (Doorenweerd et al, 2020), especially for a large number of taxonomic groups, as demonstrated here.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research on animals has indicated that mitochondrial DNA can be under strong diversifying selection (Stoeckle and Thaler 2014) and the resulting violation of molecular clock assumptions (Kimura 1983) makes molecular dating problematic (Matumba et al. 2020). Although both markers used in this study are non‐coding, cox2‐3 is linked to protein‐coding genes that are potentially under selection pressure, by virtue of being located on the same genome.…”
Section: Discussionmentioning
confidence: 99%
“…The data generated here are not considered suitable for inferring what oceanographical conditions existed along the Wild Coast during the time when the regional populations split from their sister taxa. This is because mtDNA is often under strong selection (Meiklejohn, Montooth, & Rand, 2007; Stewart, Freyer, Elson, & Larsson, 2008) and thus violates the assumption of the neutral theory of evolution (Kimura, 1983), which makes its usefulness for molecular dating questionable (Matumba, Oliver, Barker, McQuaid, & Teske, 2020). Our maximum clade credibility tree indicates that the splits may have occurred during the previous interglacial phase (~120,000 years ago) or during the subsequent glacial phase, although potential diversifying selection linked to thermal selection suggests that divergence could have taken place more recently.…”
Section: Discussionmentioning
confidence: 99%